Joint optimization algorithm for task offloading resource allocation based on edge-end collaboration - Liuqing WU; Xiaorong ZHU (Dianxin kexue)
In order to solve the problem of limited mobile terminal resources and improve task processing efficiency,a task offloading resource allocation algorithm based on edge-end collaboration was proposed.With the goal of maximizing the total benefit of tasks,the optimal task offloading resource allocation problem based on Lyapunov theory was formed by the constraint of service QoS guarantee and resource limitation.Since the problem is NP-hard,it was decoupled into a channel resource allocation problem solved by KKT condition and a 0-1 integer programming problem about task assignment.Compared with the traditional algorithm,the complexity of the proposed algorithm was O(mn),the efficiency was improved by about 20%,and the delay was reduced more than 15%.